The Quantified Behavioral Test—A Confirmatory Test in the Diagnostic Process of Adult ADHD? - Brunkhorst-Kanaan, Nathalie; Verdenhalven, Moritz; Kittel-Schneider, Sarah; Vainieri, Isabella; Reif, Andreas; Grimm, Oliver (Frontiers in Psychiatry, 2020)
The differential diagnosis of ADHD in adulthood is complicated by comorbid disorders, but also by the overlapping of main symptoms such as inattentiveness, impulsivity and hyperactivity with other disorders. Neuropsychological tests like continuous performance tests (CPT) try to solve this dilemma by objectively measurable parameters. We investigated in a cohort of n=114 patients presenting to an ADHD-outpatient how well a commercially available CPT test (QbTest®) can differentiate between patients with ADHD (n=94) and patients with a disconfirmed ADHD diagnosis (n=20). Both groups showed numerous comorbidities, predominantly depression (27.2% in the ADHD group vs. 45% in the non-ADHD group) and substance-use disorders (18.1% vs. 10%, respectively). Patients with ADHD showed significant higher activity (2.07±1.23) than patients without ADHD (1.34±1.27, dF=112; p=0.019), whereas for the other core parameters, inattention and impulsivity no differences could be found. Reaction time variability has been discussed a typical marker for inattention in ADHD. Therefore, we investigated how well ex-gaussian analysis of response time can differentiate between ADHD and other patients, showing, that it does not help to identify patients with ADHD. Even though patients with ADHD showed significantly higher activity, this parameter differed only poorly between patients (accuracy AUC 65% of an ROC-Curve). We conclude that CPTs do not help to identify patients with ADHD in a specialized outpatient clinic. The usability of this test for differentiating between ADHD and other psychiatric disorders is poor and a sophisticated analysis of reaction time did not decisively increase the test accuracy.